Celiac disease and its histopathology - Dr. Vikas Kumar; Dr. Pallavi Anand; Dr. Sangeeta Samorekar; Dr. B. P. Nag; Dr. Narayani Joshi; Dr. Renu Jain (Tropical Journal of Pathology and Microbiology, 2019)
Introduction: Celiac disease, also known as celiac sprue, non-tropical sprue, gluten-induced enteropathy, or gluten-sensitive enteropathy (GSE), is a chronic immune-mediated disorder of the small intestine characterized by malabsorption after ingestion of wheat gluten or related proteins in rye (secalins) and barley (hordeins) in individuals with a certain genetic background.Materials and Method: The study was conducted in Mahatma Gandhi Medical College and hospital, Jaipur. 53 Duodenal biopsies were taken who have symptoms of diarrhea, iron deficiency anemia, amenorrhea, recurrent mouth ulceration. All biopsies taken from duodenal sitewere brought in 10% buffered formalin. After overnight fixation in formalin, the tissues were processed in automated tissue processor for dehydration, clearing, and paraffin embedding. Sections were cut in rotary microtome 4 micrometer thickness. The section was stained for Hematoxylin and Eosin stain.Results: The present study included 53 Duodenal biopsies. Out of 53 duodenal biopsies, 12 biopsies have shown presence of Celiac disease. Rest 41 biopsies have shown chronic duodenitis.Conclusion: Celiac disease is a common autoimmune condition with mainly intestinal, but also extra-intestinal manifestations. The histologic hallmark of GlutenSensitive Enteropathy is both increased inflammation and architectural derangement in the small intestinal villi.The small intestinal mucosa of untreated persons with celiac disease usually display villous atrophy (Marsh III), or, less commonly, isolated crypt hyperplasia (Marsh II), together with intraepithelial lymphocytic proliferation.